THE EFFECTS OF OUTDOOR EDUCATION ON COGNITIVE DEVELOPMENT IN PRESCHOOL CHILDREN - Guzal Malikovna Nazirova, (The Bioscan, 2025)
Outdoor education has emerged as a transformative approach in early childhood education, offering unique opportunities for cognitive, social, emotional, and physical development. This article provides a comprehensive review of the effects of outdoor education on cognitive development in preschool children, with a focus on key areas such as executive function, problem-solving skills, attention, creativity, and language acquisition. Drawing on interdisciplinary research from psychology, education, and environmental science, we explore the mechanisms through which nature-based learning environments enhance cognitive abilities. Attention Restoration Theory, the Biophilia Hypothesis, and Embodied Cognition provide a theoretical foundation for understanding how outdoor experiences foster brain development and learning. Empirical evidence suggests that regular engagement with natural environments improves executive function, boosts creativity, enhances focus, and supports language development. Furthermore, outdoor education promotes holistic growth by reducing stress, encouraging physical activity, and fostering social interaction. This article also discusses practical implications for educators and policymakers, emphasizing the need to integrate outdoor learning into early childhood curricula, increase access to natural spaces, and provide professional development for teachers. By synthesizing current research, this review underscores the critical role of outdoor education in nurturing the cognitive and developmental potential of preschool children, offering a compelling case for its widespread adoption in early childhood education systems.